Encouraging Discussion of Science and Technology Futures through Practice-Led Research. Issue 1 (27th May 2020) - Fitzgerald, Sean
A version of this paper and associated short experimental film were presented and screened at the Media, Communication and Cultural Studies Association (MeCCSA) Conference: Media Interactions and Environments, University of Brighton, 8–10 January 2020. The refocused paper now presents a full copy of the original speculative fiction which examines an imagined physical creation of a synthetic-organic hybrid that could signal the end of the Anthropocene. The speculative fiction, 'NUCA: Beginnings in vivo, ' is set against the environments of genetic manipulation, human endeavour and synthetic biology, and the ambition to design a non-natural gene-selecting intelligence to rival the four-billion-year experiment that has produced twenty-first century Homo sapiens . The context, ideas and practice-led research are delivered through the fiction, along with the short film, NUCA: Next Universal Common Ancestor .